Exploring Innovation Trends in Public Entrepreneurship: A Bibliometric Study of Adoption and Inhibiting Factors - Sulmiah, Sulmiah; Rifdan, Rifdan; Sahade, Sahade; Rahmadani, Nanang; Hermawan, Adi (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2024)
This research aims to identify innovation trends in public entrepreneurship and explore the factors influencing adoption and the obstacles faced. The background of this research is based on the urgent need to understand how public entrepreneurship, through the adoption of innovation, can respond to increasingly complex public sector challenges. The method used is a bibliometric analysis using the VOSviewer visualization tool, which allows mapping of research trends, author collaborations, and main topic clusters. The research results show that innovation and entrepreneurship are closely related, with governance, public policy, and digitalization playing an essential role in driving innovation adoption. In addition, it was found that institutional and structural barriers often hinder the diffusion of innovation in the public sector. This research implies the need for increased collaboration between scientific disciplines and policy reforms that support a more adaptive public entrepreneurial innovation ecosystem. These findings contribute to the growing literature on innovation in the public sector and provide insights for policymakers to formulate more effective strategies.